Artificial intelligence applications in the diagnosis and treatment of bacterial infections - Zhang, Xiaoyu; Zhang, Deng; Zhang, Xifan; Zhang, Xin (Frontiers in Microbiology, 2024)
The diagnosis and treatment of bacterial infections in the medical and public health field in the 21st century continue to face great challenges. Artificial Intelligence (AI) has shown great potential as a powerful new tool in the diagnosis and treatment of bacterial infections. AI is rapidly revolutionizing epidemiological studies of infectious diseases, providing effective early warning and prevention and control of outbreaks. Machine learning models provide a highly flexible way to simulate and predict the complex mechanisms of pathogon-host interactions, which is crucial for a comprehensive understanding of the nature of diseases. Machine learning-based pathogen identification technology and antimicrobial drug susceptibility testing breaks through the limitations of traditional methods, significantly shortens the time from sample collection to result determination, and greatly improves the speed and accuracy of laboratory testing. In addition, the application of AI technology in the treatment of bacterial infections, especially in the research and development of drugs and vaccines, as well as the application of innovative therapies such as bacteriophage, provides new strategies for improving the therapeutic effect and coping with the growth of bacterial resistance. Although AI has a broad application prospect in the diagnosis and treatment of bacterial infections, there are still great challenges in data quality and quantity, model interpretability, clinical integration, and patient privacy protection. To overcome these challenges, the realization of its widely application in clinical practice, also need the interdisciplinary cooperation, technology innovation and policy support to the joint efforts of the. In summary, with the continuous development and in-depth application of artificial intelligence technology, AI will help doctors more effectively respond to the challenge of bacterial infection, promote the development of medical practice toward precision, efficiency and personalization, so as to provide the best nursing and treatment plan for patients and provide strong support for public health safety.